Identificación, biología y descripción de Melanagromyza tomaterae Steyskal (Diptera: Agromyzidae) barrenador del tomate Physalis ixocarpa Brot. - Morales Galván, Oscar; Bautista Martínez, Néstor; Valdez Carrasco, Jorge; Carrillo Sánchez, J. Luis (Instituto de Ecología, A.C., 2002)
The presence of a husk tomato (Physalis ixocarpa Brot.) stemborer is reported for the first time in Mexico. The pest is locally named “arrocillo” (little rice) in reference to the appearance of larvae and pupae. In the Mexican states of Mexico and Morelos infestations up to 70% were recorded. The husk tomato stemborer was identified as Melanagromyza tomaterae Steyskal (Diptera: Agromyzidae). The main morphological characteristics of this species were described using scanning electron microscopy. The eggs are depositedby the female in the lenticels, and the larve feeds on the stem central medulla. The larve make an exit hole which lets the imago emerge. Several generations are overlapped in a given plant. The presence of this insect is related with a tomato disease caused by Fusarium oxisporum (Sheld.). Two species of parasitoids of the families Braconidae and Pteromalidae were found in association with M. tomaterae. The weevil Trichobaris championi occurs also in this crop, and its attack added to the stemborer can reach a 90% of infestation.